2022
DOI: 10.1167/tvst.11.9.34
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping of ABCA4 Retinopathy by Machine Learning Analysis of Full-Field Electroretinography

Abstract: Purpose Biallelic pathogenic variants in ABCA4 are the commonest cause of monogenic retinal disease. The full-field electroretinogram (ERG) quantifies severity of retinal dysfunction. We explored application of machine learning in ERG interpretation and in genotype–phenotype correlations. Methods International standard ERGs in 597 cases of ABCA4 retinopathy were classified into three functional phenotypes by human ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…AI-guided genotype/variant-based characterization based on ffERGs has also been developed. 26 Thus, an AI-guided combination of retinal imaging and functional assessment can provide a more comprehensive machine diagnosis. AI has the potential to facilitate prognostic predictions in patients with Miyake disease at the earliest stages of genetic testing, which can significantly influence their life plans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AI-guided genotype/variant-based characterization based on ffERGs has also been developed. 26 Thus, an AI-guided combination of retinal imaging and functional assessment can provide a more comprehensive machine diagnosis. AI has the potential to facilitate prognostic predictions in patients with Miyake disease at the earliest stages of genetic testing, which can significantly influence their life plans.…”
Section: Discussionmentioning
confidence: 99%
“… 20 22 Deep learning techniques have proven successful in ophthalmology, 23 with machine learning–assisted diagnosis gaining widespread recognition in retinal disease management. 24 26 Accurate diagnosis of inherited retinal disease (IRD), particularly OMD, is challenging because of limited access to multidisciplinary specialist teams. Artificial intelligence (AI)–based diagnostic platforms that rely on color fundus photographs (CFPs), fundus autofluorescence (FAF) images, and SD-OCT images have been developed based on retinal images of IRDs.…”
mentioning
confidence: 99%
“…With development of newer devices (including portable and multimodal technology), and more refined, including more rapid, testing protocols, combined with novel, AI-assisted analyses, it is likely that tests will become more accessible and continue to yield valuable clinical and scientific information. This will have relevance to common and rare diseases of the eye and visual pathway, and also, given similarities between retinal and brain circuitry, potentially to wider neurological and neuropsychiatric disease [71,85,88,[92][93][94].…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence (AI) is being applied to many areas of healthcare showing high levels of accuracy, equivalent to experts. There have been investigations applying AI or machine-learning techniques to electrophysiology data [34,[85][86][87][88][89][90]. These include studies of ERG data that may have applicability in conditions including glaucoma [88], hydroxychloroquine retinopathy [87], and even autism spectrum disorder [86] and depression [89], well as studies of VEP data to improve estimation of acuity [90].…”
Section: Mathematical Models Of Phototransduction and Outer Retinal C...mentioning
confidence: 99%
“…These findings are supported by the association with genotype grouping (e.g., group 1 harboring milder variants, whereas group 3 is associated with a greater prevalence of null variants). 13 , 20 , 21 Further analysis demonstrated that those with abnormal ffERG results also showed decreased BCVA and higher rate of scotoma and atrophy enlargement than those with normal ffERG results. 15 , 22 …”
mentioning
confidence: 93%